OVEREXPRESSION OF HER2/NEU ONCOGEN, P53 AND ESTROGEN RECEPTOR IN ENDOMETRIAL HYPERPLASIA AND CARCINOMA - H. HUSSEIN, ZIHEL; A. HASSAWI, BASHAR (Journal of Duhok University, 2019)
Background: Endometrial hyperplasia with its two types (simple and complex hyperplasia with or without atypia) is one of the most important endometrial lesions. The probability of progression of endometrial hyperplasia to carcinoma is related to the degree of architectural and/or cytological atypia. There are two fundamentally different pathogenic types of endometrial carcinoma: type I (estrogen related, endometrioid type) and type II (non-estrogen related, non-endometrioid type). Recently, various biomarkers detect prognostic factors in endometrial carcinomas, such as Her2/neu, P53 as well as Estrogen Receptor (ER). Materials and Methods: During the period from November 2015 to May 2016, 101cases (as blocks) were collected from the archive of different Laboratories. There were 52 cases of endometrial hyperplasia; the other 49 cases were endometrial carcinoma. All the cases were revised histologically (using Hematoxylin and Eosin stain) to identify the types of hyperplasia and carcinoma, as well as the grade of carcinoma and the degree of myometrial invasion. Three markers were applied (Her2/neu, P53 and Estrogen Receptor) by using automated immunohistochemistry staining.Results: The predominant cases of the endometrial hyperplasia were in the 5th decade with a mean age (44.6) years. The majority were simple hyperplasia without atypia. The endometrial carcinoma cases were predominant in the 6th decade with a mean age (55.5) years. The majorities were of the classical type (65.3%) and grade II (48.9%). Her2/neu expression significantly increased in positivity (p=0.001), while P53 did not show significant changes with disease progression (p= 0.1). Estrogen Receptor immunoreactivity was decreased significantly from simple hyperplasia to carcinoma (p= 0.001). There were no correlation between these triple markers and increasing grade. Although, the number of cases showed more positivity of Her2/neu and P53 with the increasing of myometrial invasion and expression of Estrogen receptor decreased but the relation was statistically not significant (p= 0.9). Among the studied cases, there were 18.2% and 50% of complex hyperplasia without atypia and atypical hyperplasia respectively transmitted to carcinoma, while none of the simple hyperplasia cases showed transmission to carcinoma. Conclusions: Cases of the endometrial hyperplasia were more prevalent at pre and perimenopausal period while endometrial carcinoma was more prevalent in postmenopausal women. Her2/neu showed more immunoreactivity with progression of the pathological change (increasing morphological and cytological complexity) from endometrial hyperplasia to carcinoma in contrast to Estrogen Receptor expression which showed converse relationship with progression of the disease. Expression of P53 was seen to have more immunoreactivity with high grade and highly invasive tumor